The Impact of Physical Activity on Treatment Outcomes in Patients with Type 2 Diabetes - Kossakowska, Aleksandra; Leicht, Jakub; Hassan, Aisha; Hassan, Sara; Bienia, Szymon; Al-Batool, Wafa; Zarecka, Izabela; Konieczna, Klaudia (Quality in Sport, 2024)
Type 2 diabetes (T2D) is a widespread and growing health problem globally, marked by hyperglycemia, insulin resistance, and serious metabolic complications. Numerous studies confirm the positive impact of physical activity on T2D management, with aerobic and resistance exercises proving particularly effective. This study aims to review the role of physical activity in glycemic control and metabolic health in T2D patients, considering guidelines from the American Diabetes Association, as well as various physiological and psychological barriers that may limit the effectiveness of exercise programs.